Working hours, work-life conflict and health in precarious and "permanent" employment - Philip Bohle; Michael Quinlan; David Kennedy; Ann Williamson (Universidade de São Paulo, 2004)
OBJECTIVE: The expansion of precarious employment in OECD countries has been widely associated with negative health and safety effects. Although many shiftworkers are precariously employed, shiftwork research has concentrated on full-time workers in continuing employment. This paper examines the impact of precarious employment on working hours, work-life conflict and health by comparing casual employees to full-time, "permanent" employees working in the same occupations and workplaces. METHODS: Thirty-nine convergent interviews were conducted in two five-star hotels. The participants included 26 full-time and 13 casual (temporary) employees. They ranged in age from 19 to 61 years and included 17 females and 22 males. Working hours ranged from zero to 73 hours per week. RESULTS: Marked differences emerged between the reports of casual and full-time employees about working hours, work-life conflict and health. Casuals were more likely to work highly irregular hours over which they had little control. Their daily and weekly working hours ranged from very long to very short according to organisational requirements. Long working hours, combined with low predictability and control, produced greater disruption to family and social lives and poorer work-life balance for casuals. Uncoordinated hours across multiple jobs exacerbated these problems in some cases. Health-related issues reported to arise from work-life conflict included sleep disturbance, fatigue and disrupted exercise and dietary regimes. CONCLUSIONS:This study identified significant disadvantages of casual employment. In the same hotels, and doing largely the same jobs, casual employees had less desirable and predictable work schedules, greater work-life conflict and more associated health complaints than "permanent" workers. OBJETIVOS: O crescimento do número de empregos precários em países da OECD está largamente associado a efeitos negativos à saúde e segurança. Embora muitos trabalhadores em turnos tenham empregos precários, as pesquisas sobre o trabalho em turnos concentram-se em trabalhadores em tempo integral com emprego contínuo. Assim, este estudo visou a investigar o impacto do emprego precário sobre as horas de trabalho, conflito trabalho-vida pessoal e saúde, comparando empregados sem vínculo empregatício com empregados "permanentes" em tempo integral em ocupações e locais de trabalho idênticos. MÉTODOS: Foram realizadas 39 entrevistas convergentes em dois hotéis cinco estrelas. Participaram 26 empregados em tempo integral e 13 sem vínculo empregatício (temporários), com idades entre 19 e 61 anos, sendo 17 do sexo feminino e 22 do sexo masculino. As horas de trabalho variaram de 0 a 73 horas semanais. RESULTADOS: Verificaram-se diferenças acentuadas entre os informes de empregados em tempo integral e os sem vínculo empregatício sobre as horas de trabalho, conflito trabalho-vida pessoal e saúde. Os empregados sem vínculo empregatício tenderam a trabalhar um número de horas bastante irregular sobre as quais tinham pouco controle. Suas jornadas de trabalho diárias e semanais eram muito longas ou muito curtas de acordo com as exigências organizacionais. Longas jornadas de trabalho, combinadas a baixa previsibilidade e pouco controle, produziram maior desagregação da vida familiar e social e um pior equilíbrio entre trabalho-vida pessoal para os empregados sem vínculo empregatício. A falta de coordenação das jornadas em vários empregos contribuíram para acentuar estes problemas em alguns casos. Entre os problemas de saúde decorrentes do conflito trabalho-vida pessoal estavam distúrbios do sono, cansaço e regimes alimentar e de exercícios desestruturados. CONCLUSÕES: O estudo identificou grandes desvantagens do emprego sem vínculo empregatício. Trabalhando nos mesmos hotéis e ocupando praticamente as mesmas funções, os empregados sem vínculo empregatício tiveram horários de trabalho mais longos ao desejado e menos previsíveis, maior conflito trabalho-vida pessoal e mais queixas relativas à saúde que os empregados "permanentes".